Efficiency Increase of Social Infrastructure Managing Factors in Resource-Extractingregions - Svetlana U. GASNIKOVA; Svetlana V. DANILOVA; Vasilij A. NAUMOV; Vera S. PETROVA (Communications of International Proceedings, 2021)
The paper is devoted to the problems of efficiency increase of social infrastructure control in resource-extracting regions of Russia, including all northern regions of Russia. Efficiency improvement of social infrastructure in separate territorial units significantly influences economy of the whole countryin the long-term prospective. Managing social infrastructure of particularregions, as well as social objects of city-forming companies, is based on existingexperience of functioning, which takes into consideration particularities of evolution process in a particular region, with application of modern methods of effective management. Factors, described in scholastic sources of information, to a large extent reflect specifics of managing social infrastructure of the regions, but in most cases, the noted factors have not undergone noticeable changes for a very long time. The need in a significant reform of managing development factors of the social infrastructure of resource extracting regions is quite current. Therestriction program affecting welfare state, which was developed to minimize the consequences of COVD-19 epidemic, has made this problem even more serious. Accordingly, the use of scientific approach to increase the efficiency of managing social infrastructure in resource extracting regions, is still in demand and is necessary to be used in the current economic situation.
Keywords: Social Infrastructure; Resource Extracting Regions; Welfare State; Development Factors.